Attitude of the International Monetary Fund to a concept of sustainable development - Huterski, Robert (Copernican Journal of Finance & Accounting, 2013)
Review of the IMF current publications from point of view of its attitude to idea of sustainable development shows that the IMF refers very often to this concept, but gives it specific meaning that is in contradiction with the essence and objective of the idea. On one hand, the IMF glorifies acceleration of economic growth. On the other, the IMF do not ponder effects of weaknesses of contemporary global monetary system for sustainable development, although that institution arranges and protects it.